2022
DOI: 10.1051/0004-6361/202142760
|View full text |Cite
|
Sign up to set email alerts
|

The molecular gas properties in local Seyfert 2 galaxies

Abstract: Aims. We present a multiwavelength study of the molecular gas properties of a sample of local Seyfert 2 galaxies to assess if, and to what extent, the presence of an active galactic nucleus (AGN) can affect the interstellar medium (ISM) properties in a sample of 33 local Seyfert 2 galaxies. Methods. We compare the molecular gas content (MH2) derived from new and archival low-J CO line measurements of a sample of AGN and a control sample of star-forming galaxies (SFGs). Both the AGN and the control sample are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…The naive expectation that AGN feedback expels and depletes the cold gas reservoir is certainly not borne out by much of the evidence. A variety of observations have demonstrated that active galaxies, covering a wide gamut of accretion power and evolutionary states, are categorically not gas-deficient compared to inactive, star-forming galaxies of similar stellar mass (e.g., Bertram et al 2007;Krips et al 2012;Xia et al 2012;Husemann et al 2017;Shangguan et al 2018Shangguan et al , 2020bShangguan & Ho 2019;Jarvis et al 2020;Yesuf & Ho 2020;Koss et al 2021;Salvestrini et al 2022). The cold gas shows no signs of being substantially disturbed in terms of its global kinematics (e.g., Ho et al 2008;Shangguan et al 2020b;Molina et al 2021), nor does it have any trouble forming stars (e.g., Bernhard et al 2019;Grimmett et al 2020;Jarvis et al 2020;Kirkpatrick et al 2020;Xie et al 2021;Zhuang et al 2021).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The naive expectation that AGN feedback expels and depletes the cold gas reservoir is certainly not borne out by much of the evidence. A variety of observations have demonstrated that active galaxies, covering a wide gamut of accretion power and evolutionary states, are categorically not gas-deficient compared to inactive, star-forming galaxies of similar stellar mass (e.g., Bertram et al 2007;Krips et al 2012;Xia et al 2012;Husemann et al 2017;Shangguan et al 2018Shangguan et al , 2020bShangguan & Ho 2019;Jarvis et al 2020;Yesuf & Ho 2020;Koss et al 2021;Salvestrini et al 2022). The cold gas shows no signs of being substantially disturbed in terms of its global kinematics (e.g., Ho et al 2008;Shangguan et al 2020b;Molina et al 2021), nor does it have any trouble forming stars (e.g., Bernhard et al 2019;Grimmett et al 2020;Jarvis et al 2020;Kirkpatrick et al 2020;Xie et al 2021;Zhuang et al 2021).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Ellison et al (2021b) used IFU data from EDGE-CALIFA and found evidence that AGN can deplete molecular gas in the central regions of their host galaxies. Maiolino et al (1997), Koss et al (2021) and Salvestrini et al (2022) found that, on global scales, there is no evidence for depletion of molecular gas mass in AGN compared to star forming galaxies. These works support the idea that AGN can affect the molecular gas content of central regions of the AGN without necessarily affecting the total amount of molecular gas mass of the host galaxy, i.e.…”
Section: The Role Of Agn Feedback In the Local Universementioning
confidence: 99%
“…The properties of molecular gas in AGN has been explored previously in many works on both global and resolved scales (Maiolino et al 1997;Saintonge et al 2017;Ellison et al 2021b;Koss et al 2021;Salvestrini et al 2022). Ellison et al (2021b) used IFU data from EDGE-CALIFA and found evidence that AGN can deplete molecular gas in the central regions of their host galaxies.…”
Section: The Role Of Agn Feedback In the Local Universementioning
confidence: 99%
“…Conversely, local Seyferts often show ongoing or recent star formation (e.g., Davies et al 2007;Esquej et al 2014), and compelling evidence indicates that the more luminous AGNs are commonly hosted in galaxies with star formation rates (SFRs) similar to those reported in typical inactive spirals (Harrison et al 2012;Rosario et al 2012Rosario et al , 2013Husemann et al 2014;Zhang et al 2016;Stanley et al 2017;Bernhard et al 2019;Schulze et al 2019;Grimmett et al 2020;Koss et al 2021;Vietri et al 2022), or even comparable to those of starbursts (Young et al 2014;Bernhard et al 2016;Pitchford et al 2016;Shangguan et al 2020a;Kirkpatrick et al 2020;Xie et al 2021). The increasing availability of cold-gas observations targeting the carbon monoxide (CO) and neutral atomic hydrogen (H I) emission lines (e.g., Evans et al 2001Evans et al , 2006Scoville et al 2003;Ho et al 2008;Xia et al 2012;Brusa et al 2015;Husemann et al 2017;Kakkad et al 2017;Husemann et al 2019a;Shangguan et al 2020b;Salvestrini et al 2022) or measurements from indirect tracers based on dust absorption and emission (e.g., Lutz et al 2018;Shangguan et al 2018;Yesuf & Ho 2019Zhuang & Ho 2020) support the view that AGNs are preferentially observed in gas-rich and highly star-forming systems (Florez et al 2020;Jarvis et al 2020;…”
Section: Introductionmentioning
confidence: 99%